2019
DOI: 10.1590/0037-8682-0465-2018
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular retrospective analysis of hepatitis E suspected cases from the Eastern Brazilian Amazon 1993-2014

Abstract: Introduction: We evaluated the anti-hepatitis E virus (HEV) antibody prevalence and HEV-RNA in archived serum samples of non-A-C hepatitis, or suspected cases of HEV infection from the Eastern Brazilian Amazon from 1993 to 2014. Methods: Serum samples (n = 318) were tested using ELISA and immunoblotting, and screened for HEV-RNA by RT-qPCR. Results: Anti-HEV IgM and IgG were detected in 3.4% (11/318) and 5.9% (19/318) of the samples, respectively. All samples were HEV-RNA negative. Conclusions: HEV was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…HEV RNA does not last long and cannot be detected in the blood about 3 weeks after onset of symptoms. The virus continued to spread in feces for a further 2 weeks ( Souza et al, 2019 ). HEV IgM appears early and disappears over 4–5 months ( Favorov et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…HEV RNA does not last long and cannot be detected in the blood about 3 weeks after onset of symptoms. The virus continued to spread in feces for a further 2 weeks ( Souza et al, 2019 ). HEV IgM appears early and disappears over 4–5 months ( Favorov et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a discrepancy in anti-HEV seropositivity (2% to 38%) between the studies developed in Northeast and Southeast regions cannot be only attributed to socioeconomic/regional differences. Indeed, further studies employing a different EIA reported a lower anti-HEV prevalence (5.3% to 5.9%) in acute non-A-C hepatitis serum samples retrospectively analyzed [ 65 , 66 ] ( Table 1 ). Most likely, it could have been due to the lack of sensitivity/specificity of the first-generation anti-HEV IgG/IgM commercialized EIA used in the earliest serological surveys (1990–2000) ( Table 1 ).…”
Section: Hev Prevalence In the Brazilian Populationmentioning
confidence: 99%
“…After the recognition of HEV-3 as being responsible for autochthonous hepatitis E in industrialized countries [ 81 , 82 ], HEV studies in Brazil started to focus on cases of acute non-A-C viral hepatitis in order to clarify the potential role of HEV in these undiagnosed cases [ 17 , 28 , 35 ], efforts that still motivate publications nowadays [ 15 , 36 ]. In general, markers of current and/or recent HEV infection (anti-IgM HEV and HEV RNA) have been detected but at a low prevalence, indicating that HEV was not the causal agent of the majority of these acute hepatitis cases.…”
Section: Discussionmentioning
confidence: 99%